“Na guerra contra o mal [...] em marcha triunfal”: as Assembleias de Deus e a ditadura militar no Brasil (1964-1985) - Silva, Josias (2020)
The present research analyzed the political relation between the Assembly of God and the Miltary Dictatorship in Brazil (1964-1985). The Pentecostalism in Brazil has been the object of the study of human and social sciences altogether. Its vertiginous growth, over the past two decades, has been noticed, especially due to its relation with the politics in Brazil. The Census of 2010 pointed towards Assembly of God as the grandest evangelical denomination of the country, which makes it become a representative of the Brazilian Pentecostalism. However, this scenery was not the same as decades prior. In 1964, when the military dictatorship in Brazil had been established, the Pentecostals – apparently – few had been involved with politics, as it had been seen as a threat towards customs and norms of the Church. The eschatological Vision of the Assembly seemed as it had left them in a state of alienation as for political questions. With this finding, we desire, (in this project) to study which had been the oficial political positioning of the church of Assembly of God toward the military dictatorship. The research pretends to raise data of this such obscure period of the history of Brazil with the Pentecostals, to comprehend if there had been any political involvement – direct or indirect – of Assemblies of God with the government in the dictatorial years. Therefore, as primate elements in the academic onset, we will use qualitative research, having as the main documentary corpus, the journal Mensageiro da Paz, analyzing as well, bibliographical sources, documents of DOPS, Brasil Nunca Mais and journals of the institution